Handbook of research on informatics in healthcare & biomedicine - Λαζακίδου, Αθηνά Α., 1975- (Hershey PA : Idea Group Reference, 2006)
"This collection describes and analyzes recent breakthroughs in healthcare and biomedicine providing comprehensive coverage and definitions of important issues, concepts, new trends and advanced technologies"--Provided by publisher.
Περιέχει βιβλιογραφία και ευρετήριο.
Keywords: Medical informatics; Bioinformatics